Orthostatic hypotension and anti-hypertensive therapy in the elderly. - Fotherby, M. D. (BMJ Group, 1994)
The effect of withdrawing or continuing anti-hypertensive therapy on orthostatic blood pressure change in elderly hypertensive subjects was examined. Subjects meeting criteria for therapy withdrawal had supine and standing blood pressure measurements taken on treatment, and at 1, 3, 6, 9 and 12 months off treatment whilst receiving standard non-pharmacological advice to lower blood pressure. Subjects not meeting blood pressure criteria for treatment withdrawal or were unwilling to stop treatment had blood pressure measurements taken after 6 and 12 months whilst also receiving non-pharmacological advice. Orthostatic hypotension was defined as a mean systolic blood pressure fall > or = 20 mmHg on standing from a supine position. Forty-seven subjects (median age 76 years, range 65-84 years) had treatment withdrawn. Thirteen subjects (median age 73 years, range 68-82 years) continued on their treatment. Twelve months after treatment withdrawal there was a significant reduction in the number demonstrating orthostatic hypotension from 11 (23%) to four (11%) (P < 0.05), whilst the group continuing on treatment showed no change. In the withdrawal group those with orthostatic hypotension on treatment (n = 11) were older (79 versus 74 years, P = 0.05), had higher prewithdrawal systolic blood pressure (164 +/- 21 versus 147 +/- 17 mmHg, P = 0.02) compared to those without, although there was no difference in body mass index, gender, number or type of anti-hypertensive drugs taken. In elderly hypertensive subjects withdrawal of anti-hypertensive therapy and institution of non-pharmacological treatment can over several months reduce the prevalence of orthostatic hypotension.